Valuation of ecosoc rights violations in insurance and capital market criminal: An approach using the ekosob violation valuation equation in the Wanaartha Life case - Ridwan Syahbani Tamher (Journal of Law, Administration, and Social Science, 2026)
This article conducts a philosophical and socio-legal examination of the systemic violation of Economic, Social, and Cultural (Ecosoc) rights within the Indonesian capital market and insurance sector, focusing exclusively on the PT Asuransi Jiwa Adisarana WanaArtha (WanaArtha Life) default tragedy. Traditionally, corporate defaults and market manipulations such as wash trading are reductively analyzed through the rigid lenses of business law, administrative compliance, and financial loss. However, this study elevates the discourse to a fundamental human rights philosophy perspective. Through empirical observation, including direct engagement with the victims' class action and courtroom proceedings, this research uncovers how state institutions, specifically the Financial Services Authority (OJK) and the Attorney General’s Office, utilize complex financial estimations and positivistic legal interpretations as instruments to alienate the absolute rights of approximately 16,500 policyholders, resulting in a catastrophic sociological and material deprivation of Rp 15.9 Trillion. To counter the utilitarian logic often employed by the state to justify its omissions and asset confiscations, this article introduces a novel conceptual framework: The Ecosoc Violation Valuation Equation. The Equation model mathematically and philosophically just to demonstrates that the absolute dignity of human rights infinitely outweighs any financial justification, administrative rationale, or state revenue estimation (such as Non-Tax State Revenue from confiscated assets) not to professional use that applied in specific case. The findings assert that the state's failure to provide preventive protection, coupled with the subsequent execution of policyholders' assets, constitutes a severe human rights violation.